Relationship Between Library Instruction Programme and the Academic Performance of Law Students in Obafemi Awolowo University, Ile-Ife, Nigeria - Adegboye, O.A. (Ghana Library Journal, 2006)
This work examined the significance of evaluating the Library Instruction Programme (LIP) with a view to drawing a relationship between the LIP and the academic performance of students using the law students of the Obafemi Awolowo University, Ile-ife in southwestern Nigeria as a case study. The study adopted the survey design method and a total enumerate study of 342 part 5 final year law students in the 2002/2003 academic session who were expected to have been exposed to the LIP in their first year of study in the university was carried out. Using the questionnaire method, a total of 318(92.98%) retrieved questionnaire were analysed using descriptive and inferential statistics at the significant alpha level of 0.05. Findings revealed that the independent variables namely; sex age, marital status, qualification (of respondents); knowledge of LIP and content of LIP were jointly positively correlated with the students’ academic performance at R = 0.880. Also, the composite effect of the independent variables revealed a significant positive relationship at P<0.05 alpha level of significance. The independent variables accounted for 76.9% of the total variation in the dependent variable. However, four out of the six independent variables namely sex, age, knowledge of LIP and content of LIP were found to be predictors of academic performance. The study concluded that the LIP had a positive significant relationship with the law students’ academic performance. Appropriate recommendations were made which included proper allotment of time to the LIP on the University time-table including increase of contact hours with students, making LIP a credit-earning course and broadening LIP curriculum to meet students’ information needs and 21st Century worldwide standards among others.